2017
DOI: 10.3141/2647-05
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Bias: Evaluating Effectiveness of Automatic Data Collection Methods in Estimating Details of Bus Dwell Time

Abstract: Data from automated vehicle location (AVL) systems, automatic passenger counter (APC) systems, and fare box payments have been heavily used to generate dwell time models with the goal of recommending improvements in efficiency and reliability of bus transit systems. However, automatic data collection methods may result in a loss of detail with regard to the dynamics of passenger activity, which may bias the estimates associated with dwell or passenger activity time. The purpose of this study is to understand b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The bus dwell time is crucial to estimate bus station capacity [38], [39], and it is, moreover, a key component of bus travel time [40]- [42]. Furthermore, the dwell time functions play a critical role in the transit assignment models and analysis for transit reliability [43]- [45]. Consequently, the estimation of bus dwell time is vital for public transport designers and bus operators.…”
Section: Dwell Time Variationmentioning
confidence: 99%
“…The bus dwell time is crucial to estimate bus station capacity [38], [39], and it is, moreover, a key component of bus travel time [40]- [42]. Furthermore, the dwell time functions play a critical role in the transit assignment models and analysis for transit reliability [43]- [45]. Consequently, the estimation of bus dwell time is vital for public transport designers and bus operators.…”
Section: Dwell Time Variationmentioning
confidence: 99%
“…Bus dwell time studies are more commonly found in the literature, in which automatic vehicle location (AVL) and automatic passenger counting (APC) data were the main data sources. However, AVL and APC data tend to overestimate passenger service (or activity) time compared with manual data ( 9 ). The first empirical study that investigated the impact of crowding and stop design on tram dwell time was carried out in Melbourne ( 3 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even the manually collected data, often used in the past [i.e., prior to the proliferation AVL/APC systems (Levinson 1983)], have found much use in applications. It is also worth noting that although AVL/APC system data processing is more cost-effective, the data extracted from these systems tend to mislead analysts into overestimating waiting times, in particular for buses (Grisé and El-Geneidy 2017).…”
Section: Introductionmentioning
confidence: 99%